20 A survey exploring patients' and healthcare professionals' attitudes towards placebo treatments. Issue 12 (14th November 2022) - Huys, Anne-Catherine ML; Franklin, Hannah D; Bhatia, Kailash P; Stone, Jon; Edwards, Mark J
Abstract : Objectives: Evaluate patients' and healthcare professionals' attitudes towards deceptive and open-label placebo treatments, its perceived effectiveness and current use. Methods: A sixteen-item anonymous survey explored attitudes towards deceptive and open-label placebo treatments in clinical practice, its perceived effectiveness and current use. The following groups completed the survey: 288 people with a neurological condition, 138 people with a functional neurological disorder, 61 people with a medical condition, 59 healthy controls and 112 healthcare professionals, of which 45 neurologists and 20 psychiatrists/psychologists. Results: The overall attitude to deceptive placebo treatments was favourable amongst non-professionals (69% in favour). The healthcare professionals were more conservative, with only 48% being in favour. However, a considerable number strongly opposed deceptive placebo: 15% of medical patients, 11% of neurological patients and 22% of patients with a functional neurological disorder. Forty-one percent of functional neurological disorder patients, 46% of patients with presumed organic conditions and 70% of healthy controls believed that a deceptive placebo would improve their own symptoms. Healthcare professionals estimated that deceptive placebo treatments would be effective in 31% of purely organic symptoms and in 55% of purely functional symptoms. Major concerns surrounding deceptive placebo involved undermining trust in the medical profession. There was marked scepticism with regards to open-label placebo in all groups, with the general underlying belief that open-label placebo is fairly ineffective. Two-thirds of healthcare professionals had never used deceptive nor open-label placebo. Those who had used it, had done so rarely and mostly for non-specific or functional symptoms or for diagnostic purposes. Conclusions: Despite a generally perceived high effectiveness of deceptive placebo treatments, its prohibition in the UK seems to be in line with general concerns and some strong opposition. Future studies will show if the negative attitude to open-label placebo is justified or if this ethically viable option deserves more consideration.